2020
DOI: 10.5604/01.3001.0014.3964
|View full text |Cite
|
Sign up to set email alerts
|

Organizational climate, organizational support and citizenship behavior in the army

Abstract: The main aim of this study is to determine how citizenship behaviors may be shaped in the Armed Forces. The presented study is by far the first that thoroughly examines connections between all aspects of organizational climate (OC), perceived organizational support (POS), and organizational citizenship behavior (OCB) in the Polish Army. Research hypotheses were examined using data collected from a sample of 139 military officers from the Polish Land Forces. Results showed that some of the OC parameters and POS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…It explains that academics would do extra job and avoid personal gains if they enjoyed fair treatment from their university leadership. A similar result was reported by prior researchers (Damayanti and Dewi, 2020;Piotrowski, et al, 2020). For instance, Damayanti and Dewi (2020) ascertained the influence of fairness on organizational citizenship behaviour in a service and capital investment company, Gianyar Regency, Bali Province, Indonesia.…”
Section: Test Of Hypothesessupporting
confidence: 84%
See 3 more Smart Citations
“…It explains that academics would do extra job and avoid personal gains if they enjoyed fair treatment from their university leadership. A similar result was reported by prior researchers (Damayanti and Dewi, 2020;Piotrowski, et al, 2020). For instance, Damayanti and Dewi (2020) ascertained the influence of fairness on organizational citizenship behaviour in a service and capital investment company, Gianyar Regency, Bali Province, Indonesia.…”
Section: Test Of Hypothesessupporting
confidence: 84%
“…This suggests that academics would voluntarily and actively engage in providing lasting solutions to their university problems if they enjoyed the goodwill of their universities. The prior survey supported the result of this research (Harmius, et al, 2021;Piotrowski, et al, 2020;Obeng, et al, 2020;Nabilla and Riyanto, 2020); that perceived organizational support has recorded a positive, significant relationship with organizational citizenship behaviour in various work settings.…”
Section: Test Of Hypothesessupporting
confidence: 74%
See 2 more Smart Citations
“… Schaufeli et al, 2009 , studying police officers and using the theory of perceived organizational support (POS), conservation of resource (COR), and job demands-resources (JD-R) model, found that POS not only directly affected police job burnout but also indirectly affected police job burnout through job satisfaction. Studying Polish military officers, Piotrowski et al (2020a) found that organizational support and climate were important for citizenship behaviors in the army. Drawing commanders’ and superiors’ attention to these aspects of the army functioning may help them to shape and promote citizenship behaviors in a better way.…”
Section: Literature Reviewmentioning
confidence: 99%